1990
DOI: 10.1073/pnas.87.18.7185
|View full text |Cite
|
Sign up to set email alerts
|

High-affinity transport of glutathione is part of a multicomponent system essential for mitochondrial function.

Abstract: Glutathione, an essential cellular antioxidant required for mitochondrial function, is not synthesized by mitochondria but is imported from the cytosol. Rat liver mitochondria have a multicomponent system that underlies the remarkable ability of mitochondria to take up and retain glutathione. At external glutathione levels of <1 mM, glutathione is transported into the mitochondrial anatrix by a high-affinity component (K., -'60 FM-; V ,K, 0.5 nmol/min per mg of protein), which is saturated at levels of 1-2 mM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
155
0
2

Year Published

1997
1997
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(163 citation statements)
references
References 37 publications
6
155
0
2
Order By: Relevance
“…Mitochondrial GSH/GSSG plays an important role in redox buffering and redox signaling. In humans, glutathione depletion has been associated with renal, hepatic, and brain tissue damage along with degradation of mitochondria (22,23). Severe impairment of glutathione homeostasis and changes in glutathione-dependent antioxidant defense have been found to be associated with Friedreich's ataxia (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial GSH/GSSG plays an important role in redox buffering and redox signaling. In humans, glutathione depletion has been associated with renal, hepatic, and brain tissue damage along with degradation of mitochondria (22,23). Severe impairment of glutathione homeostasis and changes in glutathione-dependent antioxidant defense have been found to be associated with Friedreich's ataxia (24).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria do not possess the enzymes required for de novo GSH synthesis, 40 but utilize cytosolic GSH derived from a multicomponent, ATP dependent, mitochondrial transporter that translocates GSH from the cytosol into the mitochondrial matrix. 41,42 The transporter has a high affinity component which functions at low cytosolic GSH levels, to maintain mitochondrial GSH levels during periods of cytosolic GSH depletion. 41 Evidence for this transporter function in PW cells is provided by the observation that after cytosolic GSH depletion, the enriched mitochondrial GSH fraction still contains approximately 25% of the pretreatment GSH content compared with untreated control samples.…”
Section: Discussionmentioning
confidence: 99%
“…41,42 The transporter has a high affinity component which functions at low cytosolic GSH levels, to maintain mitochondrial GSH levels during periods of cytosolic GSH depletion. 41 Evidence for this transporter function in PW cells is provided by the observation that after cytosolic GSH depletion, the enriched mitochondrial GSH fraction still contains approximately 25% of the pretreatment GSH content compared with untreated control samples. After 48 h of treatment with BSO, GSH was undetectable in mitochondrial fractions.…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the mitochondrial enzyme hydrolyzes S-D-lactoylglutathione that has diffused or been transported into the mitochondrial matrix from the cytosol (12). It has also been suggested that uptake of S-D-lactoylglutathione is a possible pathway for the mitochondrial import of GSH (12), although direct import of GSH also occurs (32). Alternatively mitochondrial glyoxalase II activity may be required to hydrolyze thiol esters of glutathione formed by non-enzymatic or enzymatic acyl transfer from mitochondrial thiol esters of coenzyme A (9).…”
Section: Fig 3 Immunoblotting Of Glyoxalase Ii-luciferase Fusion Prmentioning
confidence: 99%